Detailed microstructure analysis and 3D simulations of porous electrodes - Joos, Jochen; Carraro, Thomas (ECS transactions, 2011)
The microstructure of a high performance LSCF-cathode is reconstructed using a dual-beam focused ion beam / scanning electron microscopy (FIB/SEM) system. The corrected reconstruction data representing altogether a volume of ~ 2800µm3 are the basis for the calculation of the microstructure parameters (i) volume-specific surface area, (ii) volume/porosity fraction and (iii) tortuosity. An analysis of the influence of the size of the reconstructed volume on the microstructure parameters is performed. Thereby the FIB/SEM data were resampled with different sizes and the influence of the resampling on the parameters is investigated. These parameters constitute the basis to calculate cathode performance via simplified microstructure models (1). However, it would be desirable to fit the reconstructed microstructure directly into a more accurate 3D-model. First results of a 3D finite element method model, which enables a direct use of the corrected 3D FIB/SEM data, are presented here.